Interpersonal relationship skills building program: An experimental study - Flores, Ma. Erlinda M. (Animo Repository, 1982)
The purpose of this study was to develop, implement, and evaluate an interpersonal relationship skills building program for adolescent high school students of St. Mary's Academy, Pasay City. More specifically, the purpose of the training program was to provide maximum opportunity for the participants to achieve and demonstrate social skills, namely, an adequate self-concept, express self-disclosure messages, and develop coping skills that include effective communication, acceptance of others, sensitivity and empathy, and ability to work effectively in a group, that are essential in human relationships. The subjects in the study were 30 first year high school students who were randomly selected from among those who got low average profiles in both tests. Fifteen subjects received the three weeks of training and the other 15 subjects served as a wait list control group who were offered the course later in the second semester. Prior to the beginning of the training program and immediately following the program, subjects in the experimental and control groups were given two sets of questionnaires to be accomplished: Interpersonal Relationship Skills Inventory (IRSI) - a researcher- constructed questionnaire that measures some basic interpersonal skills essential in human relations, and the Interpersonal Communication Inventory (ICI) that measures the process of communication as an element of social interaction. In addition, an evaluation of the program was completed by the participants to determine areas pertinent to the program and evaluate further the effectiveness of the program.Employing t-test for dependent and independent samples to compare the performance of both groups, the subjects in the experimental group who received the training were able to demonstrate skills functioning in all areas at a significantly (p .01) higher level than those in the nontrained control group. They were able to (1) acquire an adequate self-concept, (2) express self-disclosure messages, (3) accept others as they are, (4) deve